2019
DOI: 10.2147/prbm.s191037
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of severe moral distress among healthcare providers in Saudi Arabia</p>

Abstract: BackgroundMoral distress is a serious problem in healthcare environments that requires urgent attention and management. It occurs when healthcare providers are unable to provide the care that they feel is right or take, what they believe to be, ethically appropriate actions for their patients. Thus, this study aims to examine moral distress among nurses and physicians working in tertiary teaching hospitals in Saudi Arabia, as well as to evaluate the level of association between moral distress and turnover.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
1
33
2
4
Order By: Relevance
“…The results of the present study reinforce this: Neurological residents who considered leaving the field of inpatient-care were older and had worked longer as physicians. The study could not show that considerations of leaving inpatient-care correlated with a higher average level of disturbance as previous studies had shown [ 22 , 36 ]. However, in the present study residents who considered leaving the field of inpatient-care experienced the mentioned conflict situations on average significantly more frequently.…”
Section: Discussioncontrasting
confidence: 86%
“…The results of the present study reinforce this: Neurological residents who considered leaving the field of inpatient-care were older and had worked longer as physicians. The study could not show that considerations of leaving inpatient-care correlated with a higher average level of disturbance as previous studies had shown [ 22 , 36 ]. However, in the present study residents who considered leaving the field of inpatient-care experienced the mentioned conflict situations on average significantly more frequently.…”
Section: Discussioncontrasting
confidence: 86%
“…Similarly, Bickhoff et al (13) and Escobar-Chua (12,13) described how nursing students lack moral courage due to their novice status, fear of consequence, lack of confidence and experience, and how moral distress drives students to avoid ethical conflicts. Although the position of junior nurses is not the same as that of nursing students, they both lack experience in acting morally courageously and possibly undergo a comparable experience when confronted with situations that provoke moral distress (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on moral distress have shown that it was prevalent among all healthcare providers. A recent study conducted in Tehran has shown that nurses working in hospital have higher levels of Moral Distress [ 31 ], while Almutairi et al [ 32 ] have reported a moderate level of Moral Distress.…”
Section: Discussionmentioning
confidence: 99%